Self-efficacy and motivation to volunteer among undergraduate students - Kang, Tan Zi; Kahar, Rojanah (Human Resource Management Academic Research Society, 2022)
Study shows that self-efficacy and motivation have emerged to be predictors of volunteering intention. This study aims to determine the relationship between self-efficacy and motivation to volunteer among undergraduate students. A total of 359 respondents were selected by using cluster sampling technique. The data for this study were collected by using a self-administered questionnaire. General Self-Efficacy Scale by Jurusalem & Schwarzer (1995) was used to measure students’ level of self-efficacy, while the motivation to volunteer was measured with Volunteer Functions Inventory by Clary et.al (1998). The results indicated that self-efficacy correlates significantly with motivation to volunteer in all the dimensions (protective, values, career, social, understanding and enhancement). Findings emphasize the concept of boosting self-efficacy as measures in reducing the lack of participation in volunteerism among university students.